Mechanism of leakage current increase in p-GaN gate AlGaN/GaN power devices induced by ON-state gate bias. (29th October 2018) - Tang, Xi; Li, Baikui; Moghadam, Hamid Amini; Tanner, Philip; Han, Jisheng; Li, Hui; Dimitrijev, Sima; Wang, Jiannong
Abstract: An increase in OFF-state leakage current in p-GaN gate AlGaN/GaN high-electron-mobility transistors (HEMTs), induced by ON-state gate bias, was observed and reported in this paper. Higher OFF-state leakage current was observed with higher gate bias voltage and longer bias duration. We propose that the initial increase in OFF-state leakage current and its subsequent decay with time are due to persistent photoconductivity effects in GaN induced by hole injection and electroluminescence during the ON-state gate bias. At room temperature, it took more than 20 s for the increased leakage current to reduce to its equilibrium level in the dark. The related physical mechanisms underlying this phenomenon in the p-GaN gate HEMT structure are also proposed.